FOLFOX and intensified split-course chemoradiation as initial treatment for rectal cancer with synchronous metastases. (3rd June 2017) - Bird, T.; Michael, M.; Bressel, M.; Chu, J.; Chander, S.; Cooray, P.; McKendrick, J.; Jefford, M.; Heriot, A.; Steel, M.; Leong, T.; Ngan, S.
Abstract: Background: Optimal initial management of rectal carcinoma with synchronous metastases (RCSM) is controversial – both for patients being treated with curative and palliative intent. This study aims to evaluate the use of an upfront treatment strategy combining FOLFOX chemotherapy with split-course pelvic chemoradiation (FOLFOX + CRT) for patients with RCSM. Material and methods: An analysis of all patients who commenced treatment with FOLFOX + CRT at our institutions between January 2009 and June 2014 was performed. The regimen consisted of a total of 12 weeks of treatment with split-course pelvic chemoradiation (50.4Gy with concurrent oxaliplatin and 5-FU) alternating with FOLFOX chemotherapy. Restaging imaging was performed following treatment, with subsequent management as per local standard of care. Results: 78 patients (15 with resectable liver-only metastases) were identified. 77 (99%) completed at least 45Gy of radiation and 87% completed ≥75% of planned dose intensity of both oxaliplatin and 5FU. Two (2.6%) patients died within 30 days of treatment. Rates of radiological complete or partial response for local and metastatic disease were 90% and 66%, respectively. 24% patients had radiological disease progression of metastatic disease. Median overall survival for patients with unresectable metastatic disease at baseline was 23 months (95%CI: 19–28). 12 patients underwent radical surgery to both the rectum and liver and had an estimated 3-year overall survival rate of 62% (95%CI: 37–100). For those patients who did not proceed to rectal surgery, only 7% required palliative re-irradiation or surgery at a later date and all >20months from initial treatment. Conclusions: In patients with unresectable metastatic disease, FOLFOX + CRT provides durable pelvic control for the majority without the need for additional local treatment. For patients with an advanced primary tumor and synchronous resectable liver-only metastases, FOLFOX + CRT can be considered a feasible and tolerable upfront treatment option.